2011
DOI: 10.1182/blood-2010-09-305128
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput mutation profiling of CTCL samples reveals KRAS and NRAS mutations sensitizing tumors toward inhibition of the RAS/RAF/MEK signaling cascade

Abstract: Cutaneous T-cell lymphomas (CTCLs) are malignancies of skin-homing lymphoid cells, which have so far not been investigated thoroughly for common oncogenic mutations. We screened 90 biopsy specimens from CTCL patients (41 mycosis fungoides, 36 Sé zary syndrome, and 13 non-mycosis fungoides/Sé zary syndrome CTCL) for somatic mutations using OncoMap technology. We detected oncogenic mutations for the RAS pathway in 4 of 90 samples. One mycosis fungoides and one pleomorphic CTCL harbored a KRAS G13D mutation; one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
59
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 47 publications
9
59
0
3
Order By: Relevance
“…We did not find any known mutation in PIK3CA, AKT1, PTEN, KRAS and BRAF genes in any cell line. The described 14 NRAS mutation Q61K was confirmed in the HuT78 cell line, but was absent from the other PTCL cell lines (data not shown). Although no mutations have yet been reported in the PIK3CD gene, 15 two described variants 16 were also studied in PTCL cell lines.…”
Section: Phosphatidylinositol-3-kinase As a Potential Therapeutic Tarmentioning
confidence: 73%
“…We did not find any known mutation in PIK3CA, AKT1, PTEN, KRAS and BRAF genes in any cell line. The described 14 NRAS mutation Q61K was confirmed in the HuT78 cell line, but was absent from the other PTCL cell lines (data not shown). Although no mutations have yet been reported in the PIK3CD gene, 15 two described variants 16 were also studied in PTCL cell lines.…”
Section: Phosphatidylinositol-3-kinase As a Potential Therapeutic Tarmentioning
confidence: 73%
“…Staining intensity was significantly higher for the MEK/ERK than for the PI3K/mTOR pathway (MEK/ERK 1.2 ± 0.2 PI3K/ mTOR 0.86 ± 0.3 P = 0.015), suggesting a predominance of this pathway in NRAS mutant melanomas stained. Recent studies demonstrate that cells with activating mutations in the RAS pathway respond to MEK inhibitors; however, in melanoma, this is especially true for RAF mutant tumors with no other activating alternations (12,30,31). To test whether NRAS mutant melanoma cell lines are sensitive to MEK inhibition, we characterized their response to two different MEK inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In CTCL, various cytogenetic studies found multiple genetic alterations that recur in a subset of mycosis fungoides and/or S ezary syndrome patients (36)(37)(38). But few common genetic variants including targetable mutations have been identified (39).…”
Section: Discussionmentioning
confidence: 99%